Preparation, in-vitro bioactivity and mechanical properties of reinforced 45S5 bioglass composite with HA-ZrO2 powders - Prasad S.; Vyas V.K.; Mani K.D.; Ershad Md.; Pyare R. (My University, 2025)
Bioglass(45S5)-Hydroxyapatite(HA)-Zirconia(ZrO2) biocomposites were prepared and heat treated at 1000,1100,1200°C for 5 hour. Simulated body fluid (SBF) is used to immersed these samples for 1,3,7,14,21 days. Samples were characterized before and after immersion in simulated body fluid by using FTIR, X-ray diffraction (XRD) and scanning electron microscope (SEM). FTIR were used to observed the formation of hydroxyapatite layer (HA) on the surface of these bio composite samples. The pH of the SBF were measured by using pH meter at 1,3,7,14,21 days. Different techniques were used to measured various mechanical properties and it was found to increase with increasing HA(10,20,30,40 wt%) and ZrO2 (5,10,15,20 wt%) content. © 2017, Oriental Scientific Publishing Company. All rights reserved.